Vision in the mantispid: a sit‐and‐wait and stalking predatory insect. (27th February 2013) - KRAL, KARL
<x xml:space="preserve">Abstract</x> Mantispids (Neuroptera: Mantispidae) are remarkable insects as a result of their close resemblance to the praying mantis (order Mantodea). Although not closely related phylogenetically, as a result of similar selective pressures, both mantispids and mantids have evolved powerful raptorial forelegs for capturing insects. Another striking feature is the hypermetamorphosis in mantispid development, as well as the parasitizing behaviour of the first‐instar larvae. The present review focuses on the role of mantispid vision. First, the morphology and functional significance of the larval eyes (stemmata) are examined. In principle, the stemmata are suitable for spatial vision because of their arrangement and structure. This is then followed by a discussion of how adult mantispids are able to capture fast‐moving insects successfully, although, in contrast to the praying mantis, mantispids rely on superposition eyes rather than on apposition eyes with a frontal region of high acuity. For both larvae and adults, comparisons are made with other insect groups. The present review also addresses the role of mantispid vision as an important cue for triggering mating behaviour; accordingly, sex‐specific differences are considered. Finally, vision in the context of orientation flight is discussed.